Bacterial communities on polyethylene microplastics in mangrove ecosystems as a function of exposure sites: Compositions and ecological functions. Issue 3 (June 2022) - Deng, Hui; Fu, Qianqian; Zhang, Yuqing; Li, Dazhen; He, Jianxiong; Feng, Dan; Zhao, Yuanyuan; Yu, Huamei; Ge, Chengjun
Abstract: Over the past decades, mangrove ecosystem has been polluted by plastic debris and microplastics (MPs) due to anthropogenic activities. Yet, little information is available on the composition and functional diversity of microbial communities on the surface of MPs in this ecosystem. The present study aims to investigate the bacterial communities growing on the surface of polyethylene microplastics (PE-MPs) in water, surface sediments and at the water-sediment interface (WSI) of mangrove ecosystems. Obtained results showed distinct variations in the taxonomic composition of bacterial communities among water, surface sediments and PE-MPs exposed to the different sites in mangrove ecosystems. For PE-MPs deployed to water, the dominant phyla were Proteobacteria and Bacteroidetes, accounting for 89.2% of the total abundance, while a relatively high proportion of Proteobacteria (85.6 ± 8.4%) was found for PE-MPs in sediments. For PE-MPs at the WSI, the top five phyla were Proteobacteria, Bacteroidetes, Planctomycetes, Actinobacteria and Firmicutes. Relatively abundant microorganisms on PE-MPs at the WSI were mainly due to tidal ebb and flood increasing interactions of sediment bacteria and PE-MPs. Functional annotation of prokaryotic taxa (FAPROTAX) analysis demonstrated that the ecological functions of microbial communities inhabiting PE-MPs were exposure site-dependent. Bacteria living on PE-MPs in water and at the WSI mainly participated in carbon and nitrogen cycle process, whereas PE-MPs in sediments enriched bacteria responsible for sulphur cycle. These results presented here highlight the importance of the exposure sites to MPs-associated bacteria in mangrove ecosystems. Graphical Abstract: ga1 Highlights: Distinct microbes were found among water, sediments and PE-MPs exposed to the different sites in mangrove ecosystems. Tide-induced resuspension favoured bacterial colonization of PE-MPs at the water-sediment interface. Microbially-driven functions of PE-MPs varied as a function of exposure sites.